HIDROKSIAPATIT SEBAGAI SALAH SATU BAHAN YANG PALING UMUM DIGUNAKAN PADA CANGKOK TULANG: TINJAUAN PUSTAKA - Amalia Leni; Nasution Aini Hariyani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: A bone graft is a bone substitute material that has been widely used in bone grafting. In general, a bone graft can be resorbable and replace normal bone in the healing process within a few months, because in principle the bone graft has the nature of osteoconduction, osteoinduction, and osteogenic. One of the synthetic materials commonly used in the bone graft is hydroxyapatite (HA), which is identical to the crystal structure of hydroxyapatite from the bone. Review: Hydroxyapatite is a synthetic bone graft, which is the most used now due to its osteoconduction, hardness, and acceptability by bone. Hydroxyapatite with a general formula of Ca10(PO4)6OH2 is much similar to an inorganic component of bone matrix. HA is one of the most stable and less-soluble calcium phosphate bioceramics with a Ca/P ratio of 1.67. Synthetic versions of bone apatite have been developed to address the demand for autologous bone graft substitutes. Synthetic HA is stiff and strong, but brittle. Some solutions to this problem are to combine HA with collagen, β-tricalcium phosphate (β- TCP), Calcium phosphate (CaP) Conclusion: Hydroxyapatite is well known for bone regeneration through conduction or by acting as a scaffold for filling of defects from ancient times, but emerging trends of osteoinductive property of HA are much promising for new bone regeneration.